God - the world's future : systematic theology for a new era - Peters, Ted, 1941- (Fortress Press, 2015)
God--The World's Future has been a proven and comprehensive textbook in systematic theology for over twenty years. Explicitly crafted to address our postmodern context, Peters explains the whole body of Christian historical doctrine from within a "roleptic" framework, "hereby the gospel is understood as announcing the pre-actualization of the future consummation of all things in Jesus Christ." Peters skillfully deploys this concept not only to organize the various theological areas or loci but also to rethink doctrines in light of key postmodern challenges from ecumenism, critical historical thinking, contemporary science, and gender and sexuality issues. The Third Edition is thoroughly revised with updated chapters, additional chapters, updated annotations and bibliographies, and further elaborations in light of recent developments in method and theological reflection. This classic text opens up systematic theology in new dimensions, retrieving traditional categories and topics for a new generation of students and learners to give a fresh reading of Christian theology and articulation of the liberating message of the gospel of God's grace for the future of the world